Treatment of Infantile Inflammatory Bowel Disease and Autoimmunity by Allogeneic Stem Cell Transplantation in LPS-Responsive Beige-Like Anchor Deficiency - Bakhtiar, Shahrzad; Gámez-Díaz, Laura; Jarisch, Andrea; Soerensen, Jan; Grimbacher, Bodo; Belohradsky, Bernd; Keller, Klaus-Michael; Rietschel, Christoph; Klingebiel, Thomas; Koletzko, Sibylle; Albert, Michael H.; Bader, Peter (Frontiers in Immunology, 2017)
Inflammatory bowel disease (IBD) in young children can be a clinical manifestation of various primary immunodeficiency syndromes. Poor clinical outcome is associated with poor quality of life and high morbidity from the complications of prolonged immunosuppressive treatment and malabsorption. In 2012, mutations in the lipopolysaccharide-responsive beige-like anchor (LRBA) gene were identified as the cause of an autoimmunity and immunodeficiency syndrome. Since then, several LRBA-deficient patients have been reported with a broad spectrum of clinical manifestations without reliable predictive prognostic markers. Allogeneic hematopoietic stem cell transplantation (alloHSCT) has been performed in a few severely affected patients with complete or partial response. Herein, we present a detailed course of the disease and the transplantation procedure used in a LRBA-deficient patient suffering primarily from infantile IBD with immune enteropathy since the age of six weeks, and progressive autoimmunity with major complications following long-term immunosuppressive treatment. At 12 years of age, alloHSCT using bone marrow of a fully matched sibling donor - a healthy heterozygous LRBA mutant carrier - was performed after conditioning with a reduced-intensity regimen. During the 6-year follow-up, we observed a complete remission of enteropathy, autoimmunity, and skin vitiligo, with complete donor chimerism. The genetic diagnosis of LRBA deficiency was made post-alloHSCT by detection of two compound heterozygous mutations, using targeted sequencing of DNA samples extracted from peripheral blood before the transplantation.